Community Readiness for Local COVID-19 Management - Pozzo, Riccardo; Virgili, Vania (Frontiers in Research Metrics and Analytics, 2021)
The experience of COVID-19 has highlighted the strategic role of local administrations, in all areas of service, in directing and coordinating actions to contain the pandemic. In this brief research report, we have interpreted the theme of the issue Open when, why, to whom? Changing challenges, perspectives, and practices in a new research culture by transferring it into a local context, namely in Italy’s inner areas, whose communities had already endured the 2016-2017 seismic swarm, we will look into the issue pragmatically, because we think that in front of a COVID-19 induced fast-changing institutional environment, science and technology studies researchers have some ideas to offer. These days, we are learning important lessons in citizen science. Today, local administrators must equip themselves with the management of infrastructures (unimaginable before COVID-19) for enforcing social distance and tracking positive cases. One of the tasks that we wish to take up is determining the levels of societal readiness and the levels of integration in society of new technologies, products, and services. The pandemic requires social and cultural innovation policies that make communities ready to respond to catastrophic events on their territory—our case-study is Italy’s inner areas—through access to data, communities of practice, co-creation, reflection, and inclusion. Finally, COVID-19 ought not to undermine the work done so far to achieve Sustainable Development Goal 1 (Poverty), 3 (Health), 4 (Education), 5 (Gender), 6 (Water), 8 (Work), 10 (Inequalities) and 16 (Peace). Pope Francis has made it clear: “This is the moment to see the poor.”